Diskriminasi Terhadap Etnik Tionghoa Dalam Novel Entrok Karya Okky Madasari - Isqi Agustin Cahyaningtiyas; Candra Rahma Wijaya Putra (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2020)
This research was written with the aim of describing the state discrimination against ethnic Tinghoa in the Entrok novel and describing the purpose of the State's domination of the Chinese ethnic group. The focus of this research is firstly the state's domination of the Chinese by force, secondly the purpose of the state's domination of the ethnic Chinese. This research uses Antonio Gramsci's perspective hegemony theory. The data collection method in this research uses literature study, the researcher collects and reads a number of libraries that are related to the theory and the objects used, namely Entrok novels and the study of hegemony theory with the approach of literary sociology. In general discrimination is a difference in attitude or treatment of fellow citizens based on differences in ethnicity, class, economy, skin color and religion. The existence of discrimination against ethnic Tioghoa is based on several reasons. The validity of the assimilation during the new order became an obstacle to the ethnic Chinese to live a free life, because anything was restricted in politics, economy and culture.